Analisis Efektivitas Promosi Online dalam Meningkatkan Omset : Studi Kasus Toko Zareen Rental Baju Kebaya Jalan Poros Kabo Perumahan Swarga Bara Extension Blok i No 2 Sangatta Utara - Noer Aidah; Arif Rambang Supu; Muhammad Imam Syafi'i (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The objectives of this study are: (1) To analyze the extent to which the effectiveness of online business contributes to increasing sales turnover, and to analyze the factors that influence the success of online business strategies in increasing company profits. (2) To optimize market reach through appropriate digital marketing strategies. (3) To create added value or unique products to compete in the market. (4) Increase sales through a variety of products that suit market needs.The type of research that the author uses in this study is field research where to obtain accurate data, the author comes directly to the research location, namely the Zareen kebaya rental shop, Jalan Poros Kabo, Swarga Bara housing complex, extension block I no. 2, North Sangatta. The informants in this study were the shop owner and employees of the Zareen kebaya rental shop. In data collection, the researcher used interview, observation, documentation techniques and the data obtained, collected and processed descriptively qualitatively.Based on the results of the study, it can be concluded that online promotion at zareen kebaya rental is effective in increasing turnover through social media strategies, attractive promotions through video and photo content, customer testimonials, and responsive services that build loyalty. This method has been running well even though there are still obstacles. The obstacles experienced by the store are up and down sales, namely, monitoring demand patterns through social media, working with suppliers to increase stock, providing collections that can be worn at many events, and adjusting collections based on market trends. This strategy allows the store to continue to meet customer needs and increase sales.